Dynamin-related protein 1: A protein critical for mitochondrial fission, mitophagy, and neuronal death in Parkinson's disease. (January 2020) - Feng, Si-Tong; Wang, Zhen-Zhen; Yuan, Yu-He; Wang, Xiao-Le; Sun, Hong-Mei; Chen, Nai-Hong; Zhang, Yi
Graphical abstract: Abstract: Parkinson's disease (PD) that afflicts millions of individuals worldwide is associated with deposits of aggregate-prone proteins (e.g., α-synuclein) and with mitochondrial dysfunction in neuronal cells. Mitochondria are the main source of reactive oxygen species, provide energy for neuronal cells, and are regarded as dynamic organelles that are determined by mitochondrial fission, fusion, and mitophagy to maintain mitochondrial homeostasis. Growing evidence reveals that several dynamics-related proteins, such as dynamin-related protein 1 (Drp1), mediate mitochondrial fission, fusion, and mitophagy, to protect against neurodegeneration in PD. More importantly, not only is Drp1-mediated fission required for mitophagy that exerts a protective effect on neurons, but abnormal mitochondrial fission and mitophagy can drive neuronal survival or cell death (i.e., autophagy, apoptosis, and necroptosis), suggesting that Drp1 may play a pivotal role in the pathogenesis of PD. Also, PD-related proteins such as α-synuclein, leucine-rich repeat kinase-2, PTEN-induced putative kinase 1, and Parkin have been proven to interact with Drp1, thus contributing to mitochondrial dynamics and clearance, as well as neuronal fate. Here, we review the roles of Drp1 in mitochondrial fission, dynamics, mitophagy, bulk autophagy, apoptosis, and necroptosis for a better understanding of mitochondrial disturbances in PD-associated neurodegeneration and summarize the advances of novel chemical compounds targeting Drp1 to provide new insight into potential PD therapies.